The Uzbek Growth Puzzle - Zettelmeyer, Jeromin (Washington, D.C. : International Monetary Fund, 1998)
After the break-up of the Soviet Union, Uzbekistan's output fell less than in any other former Soviet Republic, and growth turned positive in 1996/97. Given the country's hesitant and idiosyncratic approach to reforms, this record has suprised many observers. This paper first shows that a standard panel model of growth in transition systematically underpredicts Uzbek growth from 1992-1996, confirming the view that Uzbekistan's performance consitutes a puzzle. It then attempts to resolve the puzzle by appropriately extending the model. The main result is that Uzbekistan's output performance was driven by a combination of low initial industrialization, its cotton production, and its self-sufficiency in energy.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet